2018
DOI: 10.1055/a-0591-3962
|View full text |Cite
|
Sign up to set email alerts
|

Stationäre Therapie der komplexen PTBS in Folge körperlicher oder sexualisierter Gewalt in der Kindheit: Wirksamkeit und Prädiktoren des Behandlungsverlaufs

Abstract: Trauma-focused inpatient treatment is safe and effective for patients with complex PTSD under naturalistic conditions. Yet, despite significant improvements there is a high rate of nonresponse. Future studies should further investigate the negative predictors of treatment outcome we identified. Possible ways to reduce nonresponse are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 50 publications
0
5
0
1
Order By: Relevance
“…The 21 included studies contained a total of 1714 patients from 9 RCTs and 12 uncontrolled clinical trials or treatment cohort studies. 8 , 9 , 13 , 25 – 42 Table 1 shows the study characteristics and potential moderator variables (see supplementary Table 2 for more study details).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 21 included studies contained a total of 1714 patients from 9 RCTs and 12 uncontrolled clinical trials or treatment cohort studies. 8 , 9 , 13 , 25 – 42 Table 1 shows the study characteristics and potential moderator variables (see supplementary Table 2 for more study details).…”
Section: Resultsmentioning
confidence: 99%
“…4 Several studies have shown that PTSD is associated with high levels of dissociation, both compared with non-clinical samples and patients with other psychiatric disorders. 5 8 Additionally, several studies have shown that dissociation is strongly related to the other PTSD symptoms and that these clusters wax and wane together, also in response to treatments. 9 – 13…”
Section: Introductionmentioning
confidence: 99%
“…A typical presentation following child abuse includes co-occurrence of PTSD, somatization, and dissociation [ 10 ]. Co-occurrence of these conditions can sometimes lead to more treatment-resistant symptomatology [ 11 , 12 ]. In the present study, we aimed to identify direct connections between PTSD, somatic symptoms, and dissociation to gain deeper insight into the pathological processes underlying their comorbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Selbst bei leitliniengerechter stationärer Psychotherapie bei Patienten mit komplexer PTBS finden sich Nonresponse-Raten von ca. 50 % [5]. Diese Ergebnisse können nicht zufriedenstellen.…”
Section: Introductionunclassified